Efectivenesse of three pulp capping materials on cellular response of pulp tissue - Kusuma, Andina Rizkia Putri (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Pulp capping is a treatment that utilizes medications to preserve pulp vitality. Ca(OH)2, mineral trioxide aggregate (MTA), and biodentine are presently the most common pulp capping medications. As pulp capping materials, Ca(OH)2 and MTA are known to have several weaknesses. Biodentine has been created in an effort to mitigate the drawbacks of Ca(OH)2 and MTA. Thus, the purpose of this study is to compare the efficacy of three pulp capping medications in reducing inflammation and accelerating pulp regeneration. Methods: Total 48 male Wistar rats, that were divided into 4 groups, namely 1st control group, 2nd MTA group, 3rd biodentine group, and 4th Ca(OH)2 group. Maxillary 1st molar teeth of rats were prepared using round bur no. 080 perpendicular to the tooth axis to a depth of 1mm, until a reddish color appeared on the pulp. Furthermore, pulp capping medicament was applied to the deepest points, and temporary fillings were made with Zn2(PO4)3. Decapitation was carried out on days 4 and 7 to count the number of neutrophil cells, macrophages, odontoblast-like cells, and fibroblasts. Data were analyzed using One-way ANOVA (p